Metonymy : Hidden Shortcuts in Language, Thought and Communication - Littlemore, Jeannette (Cambridge : Cambridge University Press, 2015)
'Metonymy' is a type of figurative language used in everyday conversation, a form of shorthand that allows us to use our shared knowledge to communicate with fewer words than we would otherwise need.'I'll pencil you in' and'let me give you a hand' are both examples of metonymic language. Metonymy serves a wide range of communicative functions such as textual cohesion, humour, irony, euphemism and hyperbole - all of which play a key role in the development of language and discourse communities. Using authentic data throughout, this book shows how metonymy operates, not just in language, but also in gesture, sign language, art, music, film and advertising. It explores the role of metonymy in cross-cultural communication, along with the challenges it presents to language learners and translators. Ideal for researchers and students in linguistics and literature, as well as teachers and general readers interested in the art of communication.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Metonyms; Metaphor; Figures of speech